Sanitary Waters: Is It Worth Looking for Mycobacteria? - Angela Cannas; Francesco Messina; Paola Dal Monte; Francesco Bisognin; Giorgio Dirani; Silvia Zannoli; Giulia Gatti; Ornella Butera; Vincenzo Ferraro; Carla Nisii; Elena Vecchi; Giovanna Mattei; et al. (Microorganisms)
The freshwater environment is suitable for nontuberculous mycobacteria (NTMs) growth. Their high adaptability represents a considerable risk for sanitary water systems, which are a potential vector for NTMs transmission. This study investigated the occurrence of NTMs, such as Mycobacterium saskatchewanense, in hospital water systems to support the surveillance and control of potentially pathogenic NTMs. We analyzed 722 ultrapure dialysis fluid samples from Emilia Romagna Dialysis Services. Among these, 35 samples were found to be positive for M. saskatchewanense. The strains were characterized using whole-genome sequencing (WGS) and variability analysis was carried out along the whole M. saskatchewanense genome. This investigation revealed the exclusive presence of M. saskatchewanense in these dialysis machines, with low genetic variability among all strains (with a low number of different alleles: <15). The strong similarity among the strain groups was also confirmed in the WGS-based ML tree, with very few significant nodes, and no clusters were identified. This research highlights the necessity of implementing surveillance protocols and investigating any potential link to human infections, as well as stressing the urgency of enhancing surveillance and infection control measures.